High-wear-resistance and high-toughness material, preparation method and environment-friendly wear-resistant anti-crack concrete

By isocyanate grafting and amino-modified inorganic nanofiller treatment on liquid ethylene propylene rubber, the compatibility between rubber and epoxy resin is improved, and the problem of poor compatibility between rubber and epoxy resin in the prior art is solved, which significantly improves the The wear and impact resistance of concrete.

CN119192788AInactive Publication Date: 2024-12-27WUHAN NEW BRIGHT BUILDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411303873.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the compatibility between rubber and epoxy resin is poor, which affects the wear resistance and impact cracking resistance of the material.

Method used

By isocyanate grafting and amino-modified inorganic nanofiller treatment on the liquid ethylene-propylene rubber, isocyanate groups and epoxy groups are introduced to improve the compatibility of the rubber and epoxy resin, and participate in the ring through amino-modified inorganic nanofiller. The curing cross-linking of oxygen resin forms a three-dimensional network structure, enhancing the wear and impact resistance of concrete.

Benefits of technology

It effectively improves the wear resistance and impact cracking resistance of concrete, enhances the compatibility between rubber and epoxy resin, ensures the stability and toughness of the material, and does not affect the cross-linking of epoxy resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192788A_ABST
    Figure CN119192788A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of modified rubber materials, in particular to a high-wear-resistance and high-toughness material, a preparation method and environment-friendly wear-resistant anti-crack concrete. The high-wear-resistance and high-toughness material is obtained by mixing liquid epoxy resin, an epoxy modified composite toughening material and a curing agent, in the preparation process, dicumyl peroxide is used as an initiator, allyl isocyanate is used as a grafting monomer, liquid ethylene propylene rubber is subjected to free radical grafting functionalization, isocyanate groups are introduced, and the high-wear-resistance and high-toughness material is obtained. Then primary amine on the amino-modified inorganic nanofiller and isocyanate groups are subjected to nucleophilic addition reaction, the inorganic nanofiller is connected to an ethylene propylene rubber molecular chain through stable chemical bonds, glycidyl further reacts with the isocyanate groups, epoxy groups are introduced, and the epoxy-modified composite toughening material is obtained. The introduction of the epoxy group can effectively improve the compatibility between the toughening material and the epoxy resin. By adding the high-wear-resistance and high-toughness material, the wear resistance and crack resistance of the concrete can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of modified rubber materials, and in particular to a high-wear-resistant and high-toughness material, a preparation method, and environmentally friendly, wear-resistant and crack-resistant concrete. Background Art

[0002] Epoxy resin has good wear resistance. As a wear-resistant additive, it can effectively improve the wear resistance of various materials. However, the cured product of epoxy resin is brittle and has poor impact resistance, which makes the material easily cracked by external impact. In the prior art, rubber is often added as a toughening agent to improve the crack resistance of the material. However, the compatibility between rubber and epoxy resin is poor, which not only affects the curing and cross-linking of the epoxy resin and reduces the wear resistance, but also affects the dispersion uniformity of the rubber and reduces the toughening effect. Therefore, it is necessary to modify the rubber to improve its compatibility with the epoxy resin.

[0003] Chinese patent application CN115124788A discloses a high-strength and high-toughness modified EPDM rubber, the raw material components of which include: EPDM rubber, epoxidized natural rubber, etc. If the high-strength and high-toughness modified EPDM rubber prepared in CN115124788A is used to toughen epoxy resin, the epoxidized natural rubber can improve its compatibility with epoxy resin through the epoxy groups it contains. However, EPDM rubber itself still has the problem of poor compatibility with epoxy resin, which in turn affects the material's wear resistance and impact cracking resistance. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention provides a highly wear-resistant and high-toughness material to solve the problem of poor wear resistance and crack resistance caused by poor compatibility between rubber and epoxy resin in the prior art.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a highly wear-resistant and high-toughness material comprises the following steps:

[0007] Step 1, adding liquid ethylene-propylene rubber to xylene, stirring and dissolving, passing inert gas, adding diisopropylbenzene peroxide and allyl isocyanate, reacting, after the reaction is completed, pouring the reaction mixture into acetone while hot, precipitating, purifying the precipitate, and drying to obtain isocyanate-grafted liquid ethylene-propylene rubber;

[0008] Step 2: adding isocyanate-grafted liquid ethylene-propylene rubber into xylene, stirring and dissolving, adding amino-modified inorganic nanofiller, reacting, introducing nitrogen after the reaction is completed, dripping glycidol into the reaction mixture, reacting after the dripping is completed, precipitating, purifying, and drying to obtain an epoxy-modified composite toughening material;

[0009] Step 3: Mix the liquid epoxy resin with the epoxy-modified composite toughening material and the curing agent, and stir to obtain a highly wear-resistant and high-toughness material.

[0010] Preferably, in step 1, the mass ratio of liquid ethylene propylene rubber, xylene, allyl isocyanate and dicumyl peroxide is 100:(200-300):(15-20):(0.5-1); the reaction conditions are to react at a temperature of 110-120° C. for 3-4 hours under the protection of an inert gas.

[0011] Preferably, in step 1, the inert gas includes argon; the purification includes dissolving the precipitated precipitate with xylene and then precipitating it with acetone, and repeating this process three times.

[0012] Preferably, in step 2, the mass ratio of isocyanate-grafted liquid ethylene-propylene rubber, xylene, and amino-modified inorganic nanofiller is (115-120):(250-300):(10-15), and the reaction conditions are stirring the reaction at room temperature for 20-30 hours.

[0013] Preferably, the amino-modified inorganic nanofiller comprises amino-modified nano silicon nitride.

[0014] Furthermore, the amino-modified nano silicon nitride is prepared by the following steps:

[0015] Add γ-aminopropyltriethoxysilane to an ethanol aqueous solution, adjust the pH value to 9-10, add nano silicon nitride, ultrasonically disperse, react, filter, wash, and dry after the reaction to obtain amino-modified nano silicon nitride.

[0016] Furthermore, the mass ratio of the nano silicon nitride, γ-aminopropyltriethoxysilane and ethanol aqueous solution is 14:(1.2-1.6):(100-150), and the reaction conditions are 55-65° C. for 2-4 hours.

[0017] Furthermore, the ethanol aqueous solution comprises 95 wt % ethanol aqueous solution.

[0018] Preferably, in the step 2, the mass ratio of the reaction mixture to glycidol is (375-435):(5-10), and the reaction conditions are to react at a temperature of 55-65° C. for 1.5-2.5 h under nitrogen protection.

[0019] Preferably, in step three, the mass ratio of the liquid epoxy resin, the epoxy-modified composite toughening material, and the curing agent is 100:(20-30):(15-20), and the stirring condition is stirring at a stirring speed of 300-500 r / min for 1-2 h.

[0020] Furthermore, the liquid epoxy resin includes bisphenol A liquid epoxy resin, and the curing agent includes 2-methylimidazole.

[0021] The invention also discloses a high wear-resistant and high toughness material prepared by the above-mentioned method for preparing the high wear-resistant and high toughness material.

[0022] An environmentally friendly, wear-resistant and crack-resistant concrete is prepared by using the above-mentioned high-wear-resistant and high-toughness materials.

[0023] Furthermore, a method for preparing environmentally friendly wear-resistant and crack-resistant concrete comprises the following steps:

[0024] Step (1) weighing raw materials: 300-500 parts of cement, 500-1000 parts of gravel, 400-800 parts of river sand, 100-150 parts of wood fiber, 100-150 parts of high wear-resistant and high-toughness material, 200-300 parts of tap water, 5-10 parts of water reducer, and 5-10 parts of retarder;

[0025] Step (2) After cement and river sand are uniformly mixed, tap water is added and stirred into a uniform slurry;

[0026] Step (3) adds gravel, wood fiber, high wear-resistant and high-toughness material, water reducer and retarder to the uniform slurry, stirs until uniform, and obtains environmentally friendly wear-resistant and crack-resistant concrete.

[0027] The concrete prepared by the above method uses wood fiber, which reduces the usage of non-renewable mineral resources such as gravel and river sand, thereby increasing the environmental friendliness of the concrete material and improving the strength and impact resistance of the concrete material.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] In the present invention, liquid epoxy resin is used as the main material for preparing high wear-resistant and high-toughness materials, which can effectively improve the wear resistance of concrete; toughening material rubber and inorganic nanofillers are added to the liquid epoxy resin, which can effectively improve the problem that the epoxy resin cured product is brittle and easy to crack under impact, and improve the impact cracking resistance of concrete;

[0030] In the preparation process of high wear-resistant and high-toughness materials, the rubber is modified to effectively improve the compatibility between the rubber and the epoxy resin; dicumyl peroxide is used as an initiator and allyl isocyanate is used as a grafting monomer to perform free radical grafting functionalization on the liquid ethylene-propylene rubber to introduce isocyanate groups, and then the primary amine on the amino-modified inorganic nanofiller reacts with the isocyanate group to connect the inorganic nanofiller to the ethylene-propylene rubber molecular chain with a stable chemical bond, and glycidol further reacts with the isocyanate group to introduce the epoxy group to obtain the epoxy-modified composite toughening material. The introduction of the epoxy group can effectively improve the compatibility between the toughening material and the epoxy resin, and does not affect the crosslinking of the epoxy resin while improving the toughness;

[0031] The urea group generated by the nucleophilic addition reaction of the amino-modified inorganic nanofiller with the isocyanate group can participate in the curing and cross-linking of the epoxy resin. The cured and cross-linked product can be dispersed in the cured concrete specimen in a three-dimensional network structure, thereby further enhancing the wear resistance and impact cracking resistance of the concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a process flow chart for preparing the high wear-resistant and high toughness material of the present invention;

[0033] Figure 2 A bar graph showing the wear resistance test results of the concrete specimens prepared in the present invention;

[0034] Figure 3 It is a bar chart of the impact cracking resistance test results of the concrete specimens prepared in the present invention. DETAILED DESCRIPTION

[0035] Example 1

[0036] This embodiment discloses a method for preparing a highly wear-resistant and high-toughness material, comprising the following steps:

[0037] Step 1, add liquid ethylene propylene rubber to xylene, stir and dissolve, pass dry argon, add diisopropylbenzene peroxide and allyl isocyanate, the mass ratio of liquid ethylene propylene rubber, xylene, allyl isocyanate and diisopropylbenzene peroxide is 100:200:15:0.5, react at 110°C for 4 hours under argon protection, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 5 times the mass of the reaction mixture, precipitate, heat dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain isocyanate-grafted liquid ethylene propylene rubber;

[0038] Step 2: Add isocyanate-grafted liquid ethylene-propylene rubber to xylene, stir and dissolve, then add amino-modified nano silicon nitride, the mass ratio of isocyanate-grafted liquid ethylene-propylene rubber, xylene and amino-modified nano silicon nitride is 115:250:10, stir and react at room temperature for 20 hours, the stirring speed is 150r / min, after the reaction is completed, introduce nitrogen, add glycidol dropwise to the reaction mixture, the mass ratio of the reaction mixture to glycidol is 375:5, the glycidol addition time is 30min, after the dropwise addition is completed, react under nitrogen protection at 55°C for 2.5h, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 3 times the mass of the reaction mixture, precipitate, heat-dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain an epoxy-modified composite toughening material;

[0039] Wherein, the amino-modified nano silicon nitride is prepared by the following steps:

[0040] Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, add 1mol / L sodium hydroxide aqueous solution to adjust the pH value to 9, add nano silicon nitride, the mass ratio of γ-aminopropyltriethoxysilane and 95wt% ethanol aqueous solution is 14:1.2:100, ultrasonically disperse in an ultrasonic oscillator for 20min, react at 55°C for 4h, filter after the reaction, wash with deionized water 3 times, and dry in a 60°C vacuum drying oven for 10h to obtain amino-modified nano silicon nitride;

[0041] Step three: mix bisphenol A liquid epoxy resin with epoxy-modified composite toughening material and curing agent 2-methylimidazole, the mass ratio of bisphenol A liquid epoxy resin, epoxy-modified composite toughening material and curing agent 2-methylimidazole is 100:20:15, stir at a stirring speed of 300 r / min for 1 hour to obtain a highly wear-resistant and high-toughness material.

[0042] Example 2

[0043] This embodiment discloses a method for preparing a highly wear-resistant and high-toughness material, comprising the following steps:

[0044] Step 1, add liquid ethylene propylene rubber to xylene, stir and dissolve, pass dry argon, add diisopropylbenzene peroxide and allyl isocyanate, the mass ratio of liquid ethylene propylene rubber, xylene, allyl isocyanate and diisopropylbenzene peroxide is 100:300:20:1, react at 120°C for 3h under argon protection, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 5 times the mass of the reaction mixture, precipitate, heat dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain isocyanate-grafted liquid ethylene propylene rubber;

[0045] Step 2: Add isocyanate-grafted liquid ethylene-propylene rubber to xylene, stir and dissolve, then add amino-modified nano silicon nitride, the mass ratio of isocyanate-grafted liquid ethylene-propylene rubber, xylene and amino-modified nano silicon nitride is 120:300:15, stir and react at room temperature for 30 hours, the stirring speed is 150r / min, after the reaction is completed, introduce nitrogen, add glycidol dropwise to the reaction mixture, the mass ratio of the reaction mixture to glycidol is 435:10, the glycidol addition time is 60min, after the dropwise addition is completed, react under nitrogen protection at 65°C for 1.5h, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 3 times the mass of the reaction mixture, precipitate, heat-dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain an epoxy-modified composite toughening material;

[0046] Wherein, the amino-modified nano silicon nitride is prepared by the following steps:

[0047] Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, add 1mol / L sodium hydroxide aqueous solution to adjust the pH value to 10, add nano silicon nitride, the mass ratio of γ-aminopropyltriethoxysilane and 95wt% ethanol aqueous solution is 14:1.6:150, ultrasonically disperse in an ultrasonic oscillator for 20min, react at 65°C for 2h, filter after the reaction, wash with deionized water 3 times, and place in a vacuum drying oven at 60°C for 10h to obtain amino-modified nano silicon nitride;

[0048] Step three: mix bisphenol A liquid epoxy resin with epoxy-modified composite toughening material and curing agent 2-methylimidazole, the mass ratio of bisphenol A liquid epoxy resin, epoxy-modified composite toughening material and curing agent 2-methylimidazole is 100:30:20, stir at a stirring speed of 500r / min for 1h to obtain a highly wear-resistant and high-toughness material.

[0049] Example 3

[0050] This embodiment discloses a method for preparing a highly wear-resistant and high-toughness material, comprising the following steps:

[0051] Step 1, add liquid ethylene propylene rubber to xylene, stir and dissolve, pass dry argon, add diisopropylbenzene peroxide and allyl isocyanate, the mass ratio of liquid ethylene propylene rubber, xylene, allyl isocyanate and diisopropylbenzene peroxide is 100:220:16:0.65, react at 115°C for 3.5h under argon protection, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 5 times the mass of the reaction mixture, precipitate, heat dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain isocyanate-grafted liquid ethylene propylene rubber;

[0052] Step 2: Add isocyanate-grafted liquid ethylene-propylene rubber to xylene, stir and dissolve, then add amino-modified nano silicon nitride, the mass ratio of isocyanate-grafted liquid ethylene-propylene rubber, xylene and amino-modified nano silicon nitride is 116:265:12, stir and react at room temperature for 25 hours, the stirring speed is 150r / min, after the reaction is completed, introduce nitrogen, add glycidol dropwise to the reaction mixture, the mass ratio of the reaction mixture to glycidol is 390:6, the glycidol addition time is 40min, after the dropwise addition is completed, react under nitrogen protection at 60°C for 2 hours, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 3 times the mass of the reaction mixture, precipitate, heat-dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain an epoxy-modified composite toughening material;

[0053] Wherein, the amino-modified nano silicon nitride is prepared by the following steps:

[0054] Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, add 1mol / L sodium hydroxide aqueous solution to adjust the pH value to 9.5, add nano silicon nitride, the mass ratio of γ-aminopropyltriethoxysilane and 95wt% ethanol aqueous solution is 14:1.3:115, ultrasonically disperse in an ultrasonic oscillator for 20min, react at 60°C for 3h, filter after the reaction, wash with deionized water 3 times, and dry in a 60°C vacuum drying oven for 10h to obtain amino-modified nano silicon nitride;

[0055] Step three: mix bisphenol A liquid epoxy resin with epoxy-modified composite toughening material and curing agent 2-methylimidazole, the mass ratio of bisphenol A liquid epoxy resin, epoxy-modified composite toughening material and curing agent 2-methylimidazole is 100:23:16, stir at a stirring speed of 400r / min for 1.5h to obtain a highly wear-resistant and high-toughness material.

[0056] Example 4

[0057] This embodiment discloses a method for preparing a highly wear-resistant and high-toughness material, comprising the following steps:

[0058] Step 1, add liquid ethylene propylene rubber to xylene, stir and dissolve, pass dry argon, add diisopropylbenzene peroxide and allyl isocyanate, the mass ratio of liquid ethylene propylene rubber, xylene, allyl isocyanate and diisopropylbenzene peroxide is 100:250:17.5:0.8, react at 115°C for 3.5h under argon protection, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 5 times the mass of the reaction mixture, precipitate, heat dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain isocyanate-grafted liquid ethylene propylene rubber;

[0059] Step 2: Add isocyanate-grafted liquid ethylene-propylene rubber to xylene, stir and dissolve, then add amino-modified nano silicon nitride, the mass ratio of isocyanate-grafted liquid ethylene-propylene rubber, xylene and amino-modified nano silicon nitride is 118:280:13, stir and react at room temperature for 25 hours, the stirring speed is 150r / min, after the reaction is completed, introduce nitrogen, add glycidol dropwise to the reaction mixture, the mass ratio of the reaction mixture to glycidol is 410:7.5, the glycidol addition time is 45min, after the dropwise addition is completed, react under nitrogen protection at 60°C for 2 hours, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 3 times the mass of the reaction mixture, precipitate, heat-dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain an epoxy-modified composite toughening material;

[0060] Wherein, the amino-modified nano silicon nitride is prepared by the following steps:

[0061] Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, add 1mol / L sodium hydroxide aqueous solution to adjust the pH value to 9.5, add nano silicon nitride, the mass ratio of γ-aminopropyltriethoxysilane and 95wt% ethanol aqueous solution is 14:1.4:130, ultrasonically disperse in an ultrasonic oscillator for 20min, react at 60°C for 3h, filter after the reaction, wash with deionized water 3 times, and place in a vacuum drying oven at 60°C for 10h to obtain amino-modified nano silicon nitride;

[0062] Step three: mix bisphenol A liquid epoxy resin with epoxy-modified composite toughening material and curing agent 2-methylimidazole, the mass ratio of bisphenol A liquid epoxy resin, epoxy-modified composite toughening material and curing agent 2-methylimidazole is 100:25:17.5, stir at a stirring speed of 400r / min for 1.5h to obtain a highly wear-resistant and high-toughness material.

[0063] Example 5

[0064] This embodiment discloses a method for preparing a highly wear-resistant and high-toughness material, comprising the following steps:

[0065] Step 1, add liquid ethylene propylene rubber to xylene, stir and dissolve, pass dry argon, add diisopropylbenzene peroxide and allyl isocyanate, the mass ratio of liquid ethylene propylene rubber, xylene, allyl isocyanate and diisopropylbenzene peroxide is 100:280:19:0.9, react at 115°C for 3.5h under argon protection, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 5 times the mass of the reaction mixture, precipitate, heat dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain isocyanate-grafted liquid ethylene propylene rubber;

[0066] Step 2: Add isocyanate-grafted liquid ethylene-propylene rubber to xylene, stir and dissolve, then add amino-modified nano silicon nitride, the mass ratio of isocyanate-grafted liquid ethylene-propylene rubber, xylene and amino-modified nano silicon nitride is 119:290:14, stir and react at room temperature for 25 hours, the stirring speed is 150r / min, after the reaction is completed, introduce nitrogen, add glycidol dropwise to the reaction mixture, the mass ratio of the reaction mixture to glycidol is 420:9, the glycidol addition time is 50min, after the dropwise addition is completed, react under nitrogen protection at 60°C for 2 hours, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 3 times the mass of the reaction mixture, precipitate, heat dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain an epoxy-modified composite toughening material;

[0067] Wherein, the amino-modified nano silicon nitride is prepared by the following steps:

[0068] Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, add 1mol / L sodium hydroxide aqueous solution to adjust the pH value to 9.5, add nano silicon nitride, the mass ratio of γ-aminopropyltriethoxysilane and 95wt% ethanol aqueous solution is 14:1.5:140, ultrasonically disperse in an ultrasonic oscillator for 20min, react at 60°C for 3h, filter after the reaction, wash with deionized water 3 times, and dry in a 60°C vacuum drying oven for 10h to obtain amino-modified nano silicon nitride;

[0069] Step three: mix bisphenol A liquid epoxy resin with epoxy-modified composite toughening material and curing agent 2-methylimidazole, the mass ratio of bisphenol A liquid epoxy resin, epoxy-modified composite toughening material and curing agent 2-methylimidazole is 100:28:19, stir at a stirring speed of 400r / min for 1.5h to obtain a highly wear-resistant and high-toughness material.

[0070] Comparative Example 1

[0071] This comparative example discloses a method for preparing a highly wear-resistant and high-toughness material, comprising the following steps:

[0072] Step 1, add liquid ethylene propylene rubber to xylene, stir and dissolve, pass dry argon, add diisopropylbenzene peroxide and allyl isocyanate, the mass ratio of liquid ethylene propylene rubber, xylene, allyl isocyanate and diisopropylbenzene peroxide is 100:200:15:0.5, react at 110°C for 4 hours under argon protection, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 5 times the mass of the reaction mixture, precipitate, heat dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain isocyanate-grafted liquid ethylene propylene rubber;

[0073] Step 2: adding isocyanate-grafted liquid ethylene-propylene rubber to xylene, stirring and dissolving to obtain a mixture, introducing nitrogen, adding glycidol dropwise, the mass ratio of the reaction mixture to glycidol is 375:5, the glycidol addition time is 30 min, after the addition is completed, reacting at 55° C. for 2.5 h under nitrogen protection, after the reaction is completed, pouring the reaction mixture into acetone while hot, the amount of acetone is 3 times the mass of the reaction mixture, precipitating a precipitate, hot-dissolving the precipitate with xylene, and precipitating with acetone, repeating 3 times, placing the purified precipitate in a 60° C. vacuum drying oven and drying to constant weight, to obtain an epoxy-modified toughening material;

[0074] Step three: mix bisphenol A liquid epoxy resin with epoxy modified toughening material and curing agent 2-methylimidazole, the mass ratio of bisphenol A liquid epoxy resin, epoxy modified toughening material and curing agent 2-methylimidazole is 100:20:15, stir at a stirring speed of 300r / min for 1h to obtain a highly wear-resistant and high-toughness material.

[0075] Comparative Example 2

[0076] This comparative example discloses a method for preparing a highly wear-resistant and high-toughness material, comprising the following steps:

[0077] Step 1, add liquid ethylene propylene rubber to xylene, stir and dissolve, pass dry argon, add diisopropylbenzene peroxide and allyl isocyanate, the mass ratio of liquid ethylene propylene rubber, xylene, allyl isocyanate and diisopropylbenzene peroxide is 100:200:15:0.5, react at 110°C for 4 hours under argon protection, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 5 times the mass of the reaction mixture, precipitate, heat dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain isocyanate-grafted liquid ethylene propylene rubber;

[0078] Step 2: Add isocyanate-grafted liquid ethylene-propylene rubber to xylene, stir and dissolve, then add amino-modified nano silicon nitride, the mass ratio of isocyanate-grafted liquid ethylene-propylene rubber, xylene and amino-modified nano silicon nitride is 115:250:10, stir and react at room temperature for 20 hours, the stirring speed is 150r / min, after the reaction is completed, pour the reaction mixture into acetone while hot, the amount of acetone is 3 times the mass of the reaction mixture, precipitate, heat-dissolve the precipitate with xylene, and precipitate with acetone, repeat 3 times, place the purified precipitate in a 60°C vacuum drying oven and dry to constant weight to obtain a composite toughening material;

[0079] Wherein, the amino-modified nano silicon nitride is prepared by the following steps:

[0080] Add γ-aminopropyltriethoxysilane to 95wt% ethanol aqueous solution, add 1mol / L sodium hydroxide aqueous solution to adjust the pH value to 9, add nano silicon nitride, the mass ratio of γ-aminopropyltriethoxysilane and 95wt% ethanol aqueous solution is 14:1.2:100, ultrasonically disperse in an ultrasonic oscillator for 20min, react at 55°C for 4h, filter after the reaction, wash with deionized water 3 times, and dry in a 60°C vacuum drying oven for 10h to obtain amino-modified nano silicon nitride;

[0081] Step 3: Mix bisphenol A liquid epoxy resin with the composite toughening material and curing agent 2-methylimidazole, the mass ratio of bisphenol A liquid epoxy resin, composite toughening material and curing agent 2-methylimidazole is 100:20:15, stir at a stirring speed of 300r / min for 1h to obtain a highly wear-resistant and high-toughness material.

[0082] In the above examples and comparative examples, the liquid EPDM rubber was purchased from Shanghai Zhuzi Industry and Trade Co., Ltd., model: ROCEOIL LEP60, appearance: yellow viscous liquid, viscosity (60°C): 1900 Pa·s, ethylene content: 45%, density: 0.86 g / cm 3 ; Nano silicon nitride was purchased from Shanghai Naio Nano Technology Co., Ltd., item number: NO-N-004-1, average particle size: 20 nm; bisphenol A type liquid epoxy resin was purchased from Shandong Cosmai New Materials Co., Ltd., model: E44, appearance: colorless transparent liquid.

[0083] Test example

[0084] A method for preparing concrete comprises the following steps:

[0085] Step (1) weigh the raw materials: 400 parts of cement, 800 parts of gravel, 600 parts of river sand, 120 parts of wood fiber, 130 parts of high wear-resistant and high-toughness material, 250 parts of tap water, 8 parts of water reducer, and 7 parts of retarder;

[0086] Step (2) After cement and river sand are uniformly mixed, tap water is added and stirred into a uniform slurry;

[0087] Step (3) adding gravel, wood fiber, high wear-resistant and high-toughness material, water reducer and retarder to the uniform slurry, stirring until uniform, to obtain environmentally friendly wear-resistant and crack-resistant concrete;

[0088] Among them, cement is composite silicate cement, produced by Anhui Conch Cement Co., Ltd., model: P·C32.5; gravel is purchased from Shijiazhuang Zhuohui Mining Co., Ltd., with a particle size of 8-12 mm; river sand is purchased from Hebei Qianli Mining Co., Ltd., with a specification of 8-16 mesh; wood fiber is purchased from Langfang Weichao New Materials Technology Co., Ltd., product appearance: gray flocculent fiber, item number: 15463; water reducer is polycarboxylate water reducer, purchased from Guangdong Xinruiheng New Building Materials Co., Ltd., item number: 413541, water reduction rate ≥ 28%; retarder is gluconate retarder, purchased from Jiaxing Changli Chemical Co., Ltd., item number: 2-285; high wear-resistant and high-toughness materials are respectively made of high wear-resistant and high-toughness materials prepared in Examples 1-5 and Comparative Examples 1-2, and the prepared environmentally friendly wear-resistant and crack-resistant concrete samples are respectively recorded as sample 1, sample 2, sample 3, sample 4, sample 5, sample 6, and sample 7;

[0089] A control experiment was set up: in step (3), the high wear-resistant and high-toughness material was not added, and the concrete sample obtained was recorded as sample 8;

[0090] Environmentally friendly wear-resistant and crack-resistant concrete samples 1-8 were poured into molds, vibrated on a vibration table for compaction, removed from the molds after standing for 24 hours, moved to a standard curing room for curing for 7 days, and then heated at 120°C for 10 hours to obtain concrete specimens, which were respectively recorded as specimen 1, specimen 2, specimen 3, specimen 4, specimen 5, specimen 6, specimen 7, and specimen 8. The specifications of specimens 1-8 were all 100mm×100mm×400mm. Performance tests were performed on specimens 1-8:

[0091] (1) Wear resistance test: The wear resistance of specimens 1-8 was determined by performing friction and wear tests. The friction and wear tests were performed on a UMT-5 ball-on-disc friction and wear tester. The upper specimen was a GCr15 steel ball with a diameter of 9 mm, and the lower specimen was a test piece. The friction test conditions were: load 50 N, amplitude 0.5 cm, frequency 2 Hz, and test time 20 min. The test results are shown in Table 1:

[0092] Table 1

[0093]

[0094] It can be seen from Table 1 that the high wear-resistant and high-toughness material prepared by the present invention can effectively improve the wear resistance of concrete. Using epoxy resin as the main material for preparing high wear-resistant and high-toughness materials can effectively improve the wear resistance of concrete. Compared with Example 1, when preparing high wear-resistant and high-toughness materials in Comparative Example 1, no amino-modified inorganic nanofiller was added, and no urea group participated in the curing and cross-linking of epoxy resin, the wear resistance of concrete was reduced, and the wear rate of specimen 6 was slightly increased compared with specimen 1; when preparing high wear-resistant and high-toughness materials in Comparative Example 2, no epoxy group was introduced into the composite toughening material, and the compatibility with epoxy resin was reduced, thereby affecting the curing and cross-linking of epoxy resin in concrete, and the wear resistance was reduced. The wear rate of specimen 7 was slightly increased compared with specimen 1; since no epoxy resin was added to specimen 8, the wear resistance was the worst and the wear rate was the highest.

[0095] (2) Impact cracking resistance test: The impact cracking resistance of specimens 1-8 was determined by the bending impact test method. The determination method is as follows: the free-falling hammer is a solid cylinder with a cross-sectional diameter of 30 mm and a spherical hammer head. The hammer weighs 1.4 kg. The impact height of the free-falling hammer is 400 mm. The two ends of the beam are simply supported with a clear span of 340 mm. The hammer performs free fall in a steel hollow cylinder. At the same time, the cylinder is used to control the falling height of the hammer. A 100 mm × 100 mm thick piece of steel is placed at the bottom of the cylinder. The steel plate of m×10mm was used to prevent the hammer from hitting the concrete beam surface directly. Each impact started from the free fall of the hammer and ended when the hammer came to a complete stop. This process was repeated many times until the specimen cracked. The test result evaluation method was as follows: (1) initial crack, the beam went from no crack to micro cracks; (2) cracking, when the transverse main crack of the beam penetrated to the upper surface of the beam, the beam was said to have undergone impact cracking. The cracking of the beam was judged by observing with the naked eye through a magnifying glass whether the crack penetrated the entire cross section. The test results are shown in Table 2:

[0096] Table 2

[0097]

[0098]

[0099] As can be seen from Table 2, the high wear-resistant and high-toughness material prepared by the present invention can effectively improve the impact cracking resistance of concrete. In the preparation process of the high wear-resistant and high-toughness material, the rubber is modified to effectively improve the compatibility between the rubber and the epoxy resin. The isocyanate group is first introduced into the liquid ethylene-propylene rubber molecule, and then the primary amine on the amino-modified inorganic nanofiller reacts with the isocyanate group to connect the inorganic nanofiller to the ethylene-propylene rubber molecular chain with a stable chemical bond, which plays a stable toughening role. Compared with Example 1, when preparing the high wear-resistant and high-toughness material in Comparative Example 1, no amino-modified inorganic nanofiller was added, the toughening performance was reduced, the impact cracking resistance of the concrete was reduced, and the impact number of specimen 6 was reduced compared with that of specimen 1; when preparing the high wear-resistant and high-toughness material in Comparative Example 2, no epoxy group was introduced into the composite toughening material, the compatibility with the epoxy resin was reduced, and as the degree of curing and cross-linking of the epoxy resin decreased, the impact cracking resistance of the concrete also decreased, and the impact number of specimen 7 was reduced compared with that of specimen 1; in specimen 8, since no epoxy resin was added, the impact cracking resistance was significantly reduced, and the impact number was the least.

[0100] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a highly wear-resistant and high-toughness material, characterized in that: The steps include: Step 1, adding liquid ethylene-propylene rubber to xylene, stirring and dissolving, passing inert gas, adding diisopropylbenzene peroxide and allyl isocyanate, reacting, after the reaction is completed, pouring the reaction mixture into acetone while hot, precipitating, purifying the precipitate, and drying to obtain isocyanate-grafted liquid ethylene-propylene rubber; Step 2: adding isocyanate-grafted liquid ethylene-propylene rubber into xylene, stirring and dissolving, adding amino-modified inorganic nanofiller, reacting, introducing nitrogen after the reaction is completed, dripping glycidol into the reaction mixture, reacting after the dripping is completed, precipitating, purifying, and drying to obtain an epoxy-modified composite toughening material; Step 3: Mix the liquid epoxy resin with the epoxy-modified composite toughening material and the curing agent, and stir to obtain a highly wear-resistant and high-toughness material.

2. A method for preparing a high wear-resistant and high toughness material according to claim 1, characterized in that: In the step 1, the mass ratio of liquid ethylene propylene rubber, xylene, allyl isocyanate and dicumyl peroxide is 100:(200-300):(15-20):(0.5-1); the reaction conditions are to react at a temperature of 110-120° C. for 3-4 hours under the protection of an inert gas.

3. A method for preparing the high wear-resistant and high-toughness material according to claim 1, characterized in that: In the step 1, the inert gas includes argon; the purification includes dissolving the precipitated precipitate with xylene and then precipitating it with acetone, and repeating this process 3 times.

4. A method for preparing a high wear-resistant and high toughness material according to claim 1, characterized in that: In the step 2, the mass ratio of the isocyanate-grafted liquid ethylene-propylene rubber, xylene, and amino-modified inorganic nanofiller is (115-120):(250-300):(10-15), and the reaction conditions are stirring the reaction at room temperature for 20-30 hours.

5. A method for preparing a high wear-resistant and high toughness material according to claim 4, characterized in that: The amino-modified inorganic nanofiller includes amino-modified nano silicon nitride; The amino-modified nano silicon nitride is prepared by the following steps: Adding γ-aminopropyltriethoxysilane to an ethanol aqueous solution, adjusting the pH value to 9-10, adding nano silicon nitride, ultrasonically dispersing, reacting, filtering, washing, and drying after the reaction is completed to obtain amino-modified nano silicon nitride; The mass ratio of the nano silicon nitride, γ-aminopropyltriethoxysilane and ethanol aqueous solution is 14:(1.2-1.6):(100-150), and the reaction conditions are 55-65° C. for 2-4 hours.

6. A method for preparing the high wear-resistant and high-toughness material according to claim 1, characterized in that: In the step 2, the mass ratio of the reaction mixture to glycidol is (375-435):(5-10), and the reaction conditions are to react at a temperature of 55-65° C. for 1.5-2.5 h under nitrogen protection.

7. A method for preparing the high wear-resistant and high-toughness material according to claim 1, characterized in that: In the step 3, the mass ratio of the liquid epoxy resin, the epoxy-modified composite toughening material, and the curing agent is 100:(20-30):(15-20), and the stirring condition is stirring at a stirring speed of 300-500 r / min for 1-2 hours.

8. A method for preparing the high wear-resistant and high toughness material according to claim 7, characterized in that: The liquid epoxy resin includes bisphenol A type liquid epoxy resin, and the curing agent includes 2-methylimidazole.

9. A high wear-resistant and high toughness material prepared by the method for preparing a high wear-resistant and high toughness material according to any one of claims 1 to 8.

10. An environmentally friendly wear-resistant and crack-resistant concrete, characterized in that: It is made of the high wear-resistant and high toughness material as described in claim 9.

Citation Information

Patent Citations

  • High-strength high-toughness modified ethylene propylene diene monomer and preparation method thereof

    CN115124788A